PENGARUH ASI EKSLUSIF DAN BBLR TERHADAP KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS LAKESSI KOTA PAREPARE - Irawati, Ayu; Nurbaya, Nurbaya (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2023)
Abstract: Stunting is still a major nutritional problem that affects the health of children under five. Toddlers with stunting tend to find it difficult to reach their potential for optimal growth and development, both physically and psychomotor. The purpose of this study was to determine whether there was an effect of exclusive breastfeeding history and birth weight of children with the incidence of stunting in children under five. This research is an analytic survey research with cross sectional research design with a total sample of 75 respondents using purposive sampling technique. The results showed that the history of exclusive breastfeeding with a p-value of 0.70 with an OR value of 0.398 (0.68-5.85) and birth weight obtained a p-velue value of 0.72 with an OR value of 1.469 (0.531-3.245) which it means that exclusive breastfeeding history and birth weight have a P-velue value> 0.05. It can be concluded that there is no significant relationship between history of exclusive breastfeeding and birth weight with the incidence of stunting.Abstrak: Stunting masih menjadi masalah gizi utama yang berdampak pada kesehatan anak balita. Balita stunting cenderung akan sulit mencapai potensi pertumbuhan dan perkembangan optimal baik secara fisik maupun psikomotorik. Tujuan penelitian ini adalah untuk mengetahui apakah ada pengaruh riwayat asi ekslusif dan berat badan lahir anak dengan kejadian stunting pada anak balita. Penelitian ini merupakan survei analitik dengan desain penelitian cross sectional dengan jumlah sampel 75 responden menggunakan teknik purposive sampling. Hasil penelitian diperoleh riwayat ASI Ekslusif dengan nilai p-value 0,70 dengan nilai OR 0,398 (0,68-5,85) dan berat badan lahir diperoleh nilai p-velue 0,72 dengan nilai OR 1,469 (0,531-3,245) yang artinya riwayat ASI Ekslusif dan berat badan lahir memiliki nilai P-velue >0,05 dapat disimpulkan bahwa tidak ada hubungan yang bermakna antara riwayat ASI Ekslusif dan Berat badan lahir dengan kejadian stunting.